2012
DOI: 10.1136/bmjopen-2012-000968
|View full text |Cite
|
Sign up to set email alerts
|

The Lililwan Project: study protocol for a population-based active case ascertainment study of the prevalence of fetal alcohol spectrum disorders (FASD) in remote Australian Aboriginal communities

Abstract: IntroductionAnecdotal reports suggest that high-risk drinking in pregnancy is common in some remote Australian communities. Alcohol is teratogenic and may cause a range of lifelong conditions termed ‘fetal alcohol spectrum disorders’ (FASD). Australia has few diagnostic services for FASD, and prevalence of these neurodevelopmental disorders remains unknown. In 2009, Aboriginal leaders in the remote Fitzroy Valley in North Western Australia identified FASD as a community priority and initiated the Lililwani Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 47 publications
1
100
0
Order By: Relevance
“…Stage 2 involved inter-disciplinary health and development assessments of these children, including of motor performance. The detailed Lililwan study protocol is published elsewhere [32]. Lililwan is a Kimberley Kriol word meaning 'all the little ones'.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Stage 2 involved inter-disciplinary health and development assessments of these children, including of motor performance. The detailed Lililwan study protocol is published elsewhere [32]. Lililwan is a Kimberley Kriol word meaning 'all the little ones'.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…In the current study, we considered upper-limb co-ordination (ball skill) activities to be a gross motor skill, and hence, they were assessed by a physiotherapist but were analysed in accordance with the BOT-2 manual as a fine motor skill [26]. Consideration of culture and language, assessor training and standardised administration of the BOT-2 were performed and have been described [32,35]. Assessments were performed in quiet locations at the child's school, fine motor assessments indoors and gross motor assessments outdoors under shade.…”
Section: Procedure/data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2015 study in a rural community in Australia, a FAS rate of 120 per 1 000 was reported, [24] this being the first study outside of SA to report figures close to the SA rates. In 2006, the National Institute on Alcohol Abuse and Alcoholism already raised concern for this 'large and rapidly increasing public health problem' .…”
Section: The New Millenniummentioning
confidence: 99%